Book Review of "Human Factor in Nuclear Security: Establishing and Optimizing Security Culture" - Arjun Banerjee (International Journal of Nuclear Security, 2025)
In today’s interconnected world, where the specter of nuclear proliferation casts a long shadow over global security, fortifying nuclear safeguards has become an imperative of paramount importance. At the heart of this endeavor lies the intricate interplay of human behavior within nuclear organizations—a dynamic landscape meticulously explored in Igor Khripunov’s seminal work, Human Factor in Nuclear Security: Establishing and Optimizing Security Culture. This comprehensive analysis delves into the multifaceted realm of nuclear security culture (NSC), shedding light on its evolution, application, and ongoing challenges. By elucidating the pivotal role of the human factor in shaping security outcomes, Khripunov offers invaluable insights into fortifying global nuclear safeguards and fostering a culture of vigilance and compliance.